2008
DOI: 10.1007/s11064-008-9777-7
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem Concentrations of Cholesterol are not Influenced by Genetic Ablation of the Low-Density Lipoprotein Receptor

Abstract: The LDLr is not necessary for maintaining cholesterol concentrations in the cortex or brainstem, suggesting that other mechanisms are sufficient to maintain brain cholesterol concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Although LDLR deficiency significantly increased murine brain apoE levels by ~50%, it did not alter brain cholesterol levels (Elder et al, 2007; Fryer et al, 2005; Quan et al, 2003; Taha et al, 2008). Previously, we demonstrated that there was no significant change in brain Aβ levels both before and after the onset of amyloid deposition in PDAPP transgenic mice on a LDLR-deficient background (Fryer et al, 2005).…”
Section: Discussionmentioning
confidence: 88%
“…Although LDLR deficiency significantly increased murine brain apoE levels by ~50%, it did not alter brain cholesterol levels (Elder et al, 2007; Fryer et al, 2005; Quan et al, 2003; Taha et al, 2008). Previously, we demonstrated that there was no significant change in brain Aβ levels both before and after the onset of amyloid deposition in PDAPP transgenic mice on a LDLR-deficient background (Fryer et al, 2005).…”
Section: Discussionmentioning
confidence: 88%
“…Although cholesterol crystals were observed in the white matter of the control tissue, the IR results suggest that this fraction is significant in the white matter of mice with atherosclerosis. [42][43][44] The observed changes in the lipid fraction of the brains of 6-month-old atherosclerotic mice on a standard diet could be connected to the use of the ApoE/LDLR −/− mouse model, which demonstrates severe hypercholesterolemia (>500 mg dL −1 ) and the development of advanced atherosclerotic lesions. It has an important role in the normal development and function of the nervous system, as it is one of the components of the myelin sheath.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of LDL-R also is related with decreased pre-synaptic bouton density in the hippocampus (Mulder et al 1993), as well as increased locomotor activity (Elder et al 2008). This receptor is found throughout the brain, and although highly enriched in the brainstem, no significant changes in cholesterol content was observed in this region of LDL-R À/À mice (Taha et al 2009).…”
mentioning
confidence: 96%
“…This receptor is found throughout the brain, and although highly enriched in the brainstem, no significant changes in cholesterol content was observed in this region of LDL‐R −/− mice (Taha et al . ).…”
mentioning
confidence: 97%